Fabrication and Comparative Assessment of Solid Dispersion and Nanosuspension in Solubility Enhancement of Antihypertensive Drug - Ghadlinge, Shyam; Sable, Preeti; Lahoti, Swaroop; Sangshetti, Jaiprakash (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Azilsartan, a poorly soluble angiotensin receptor blocker belonging to BCS class II, faces challenges related to low solubility and bioavailability. To address these issues, this study compares two formulation approachessolid dispersion and nanosuspension-aimed at enhancing the solubility and bioavailability of Azilsartan. Materials and Methods Nine batches of Azilsartan-solid dispersion were prepared using spray drying with HPMC E5 LV, while nine batches of nanosuspension were formulated via solvent evaporation with PVPK-30. The formulations were evaluated for particle size, polydispersity index, zeta potential, X-ray diffraction pattern, morphology, solubility, and in vitro drug release. The optimal batches, solid dispersion-6 and nanosuspension-6, were selected based on drug content and entrapment efficiency for further comparative evaluation. Results Solid dispersion-6 and nanosuspension-6 exhibited drug content of 93.23% and 95.71%, respectively. The particle sizes measured for solid dispersion-6 and nanosuspension-6 were 511.4 nm and 347.6 nm, respectively. Morphological differences between the formulations were evident in photomicrographs. Drug dissolution rates were 95.25% for solid dispersion-6, 96.14% for nanosuspension-6, and 98.14% in an in vitro dissolution study. Conclusion The nanosuspension showed greater improvement in solubility and bioavailability, highlighting its potential as a nanocarrier for Azilsartan in clinical applications.
Keywords: Azilsartan; Solid dispersion; Nanosuspension; Solubility; Hypertension